Special education international perspectives practices across the globe - Bakken, Jeffrey P. (Bingley, U.K. : Emerald, 2014)
The volume provides a comprehensive discussion of special education from across the globe. The volume includes chapters from major countries such as United States, Canada, United Kingdom, Russia and Japan as well as countries such as Nigeria, Israel and Pakistan. Discussions related to these countries will include information on origins of special education specific to that country, prevalence and incidence rates, trends in legislation and litigation, educational interventions, working with families, teacher training, a perspective on the progress of special education, and challenges that remain.
Special education today in the United States of America / James M. Kauffman ... [et al.] -- Special education today in Canada / Tim Loreman -- Special education today in Mexico / Ismael García-Cedillo, Silvia Romero-Contreras, Todd V. Fletcher -- Special education today in Guatemala / Diane Rodriguez, Kenneth Luterbach, Rocio Espinosa de Gaitan -- Special education today in the United Kingdom / Ron Smith ... [et al.] -- Special education today in Spain / Shaila Rao, Cristina M. Cardona, Esther Chiner -- Special education today in Norway / Rune Sarromaa Hausstatter, Harald Thuen -- Special education today in Sweden / Girma Berhanu -- Special education today in Switzerland / Judith Hollenweger -- Special education today in Iceland / Gretar Marinósson, Dóra S. Bjarnason -- Special education today in Ukraine / Alla Kolupayeva, Oksana Taranchenko, Elyana Danilavichute -- Special education today in Russia / Iuliia Korolkova -- Special education today in Nigeria / Festus E. Obiakor, C. Jonah Eleweke -- Special education today in South Africa / Sigamoney Naicker -- Special education today in Ghana / Ahmed Bawa Kuyini -- Special education today in Israel / Hagit Ari-Am, Thomas P. Gumpel -- Special education today in the kingdom of Saudi Arabia / Turki A. Alquraini -- Special education today in Turkey / Macid Ayhan Melekoglu -- Special education today in India / Ajay Das, Rina Shah -- Special education today in Bangladesh / Md. Saiful Malak -- Special education today in Australia / Umesh Sharma -- Special education today in New Zealand / Garry Hornby -- Special education today in China / Mian Wang, Yajing Feng -- Special education today in Thailand / Kullaya Kosuwan, Yuwadee Viriyangkura, Mark E. Swerdlik.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Special education; Learning disabled -- Education